2006
DOI: 10.1177/106689690601400110
|View full text |Cite
|
Sign up to set email alerts
|

Granulomatous Interstitial Nephritis: A Clinicopathologic Study of 46 Cases from a Single Institution

Abstract: Acute interstitial nephritis is commonly seen in kidney biopsies of patients with acute renal failure; however, granulomatous interstitial nephritis (GIN) is rare. We identified 46 cases of GIN in a 17-year period in this institution and we investigated their most probable etiologies. Complete clinical information was available in 38 patients. Seventeen of 38 patients (44.7%) were classified as drug-induced. Renal sarcoidosis was responsible for 28.9% of cases, and the remaining 15.9% of cases included Wegener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
106
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(112 citation statements)
references
References 16 publications
1
106
1
4
Order By: Relevance
“…Although the presence of granulomas is an infrequent finding in renal biopsies, it may help to narrow the differential diagnosis. 17 Bijol et al 18 reported that drug-induced interstitial nephritides tend to have a diffuse distribution, with many eosinophils and neutrophils, as well as ill-formed granulomas, but the granulomas in our patient were well formed and have a focal distribution, with a few eosinophils and neutrophils. Granulomatous interstitial nephritis (GIN) is reported in between 0.5% and 0.9% of native renal biopsies, 19 in 0.6% of renal transplant biopsies, 20 and in chronic lymphocytic leukemia, and it also is seen in an idiopathic form.…”
Section: Pathologic Findingsmentioning
confidence: 80%
See 3 more Smart Citations
“…Although the presence of granulomas is an infrequent finding in renal biopsies, it may help to narrow the differential diagnosis. 17 Bijol et al 18 reported that drug-induced interstitial nephritides tend to have a diffuse distribution, with many eosinophils and neutrophils, as well as ill-formed granulomas, but the granulomas in our patient were well formed and have a focal distribution, with a few eosinophils and neutrophils. Granulomatous interstitial nephritis (GIN) is reported in between 0.5% and 0.9% of native renal biopsies, 19 in 0.6% of renal transplant biopsies, 20 and in chronic lymphocytic leukemia, and it also is seen in an idiopathic form.…”
Section: Pathologic Findingsmentioning
confidence: 80%
“…21 The rise in creatinine level preceded the introduction of ciprofloxacin, and the level continued to rise after metronidazole was discontinued. 18 Nonetheless, we cannot exclude 5-ASA as the cause, because the patient has not resumed taking that drug and remains stable.…”
Section: Pathologic Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bijol et al reported an incidence of granulomatous interstitial nephritis in approximately 0.5% of their medical renal biopsy specimens [8]. In retrospective case series of renal granulomas, most granulomas were categorized as drug-induced [8][9][10], and sarcoidosis was responsible for 9% to 29% of cases. A significant proportion of granulomas, 8% to 25%, were categorized as idiopathic.…”
Section: Discussionmentioning
confidence: 99%